PENGARUH GDP PER KAPITA, HARGA DAN NILAI TUKAR TERHADAP VOLUME EKSPOR BIJI KAKAO SULAWESI SELATAN KE MALAYSIA - Andi Ririn Oktaviani (Jurnal Bisnis dan Kewirausahaan, 2015)
This study aims to determine the effect of GDP per capita, price and exchange rate to the volume of South Sulawesi cocoa exports to Malaysia. Data collection methods used in this research is a method of collecting documentation based on the theory by Riduwan (2006), while the analysis method used is descriptive quantitative and qualitative methods . The results showed that before the export tax changes in 2010 the volume of exports to Malaysia a positive effect on GDP per capita of Malaysia, on the contrary after the export tax changes in 2010 the volume of exports to Malaysia negative effect on GDP per capita of Malaysia. The volume of exports to Malaysia in 2008 to 2009 negatively affect world cocoa prices, then in 2009 to 2010 the volume of exports to Malaysia a positive effect on the world price of cocoa export tax and after the change in 2010 the volume of exports to Malaysia negatively affect the world price of cocoa. Malaysian ringgit exchange rate from 2008 to 2012 or before and after the 2010 tax changes negatively affect the volume of South Sulawesi to Malaysia about cocoa exports.